"Building Core-Competencies for Sustainability through Leadership and Teamwork - the Experience of a leading ODL Institution's Star Faculty - Wardah Mohamad,; Zorah Abu Kasim, (2012)
Malaysia’s quest for achieving the status of a developed nation and increasing competition in the workforce has spurred working adults to enroll in higher learning institutions. Due to work and time constraints, most of these learners have chosen to opt for open and distance learning where they can engage in their studies while continuing to work at the same time. Open University Malaysia, as the leading ODL institution in the country, strives to fulfill its learners’ expectations while at the same time trying to forge ahead with limitations in terms of workforce, technological changes and increased competition faced by most ODL institutions. Taking these limitations in mind and realising that its future sustainability lies in its core competencies, the university’s Faculty of Business and Management has undertaken a massive move to build these competencies. Through sheer hard work and determination, the faculty has risen to be a “star” faculty in the university – showing improvements in terms of quality assessment and learning materials matched with an increase in student numbers and student satisfaction. This study shares their experiences and their secrets to success. Theirs is a journey of transformational leadership and teamwork, where two leaders lead from the front and behind - propelling a strong team towards a journey that will lead to the future. (Abstract by authors)